HOW DOES FOREIGN TRADE VOLUME AFFECT YOUTH UNEMPLOYMENT IN G-8 COUNTRIES? (Third Sector Social Economic Review, 2022)
With the phenomenon of globalization in the world, and thus as a result of the increase in capital movements, significant effects have also come into play in the foreign trade sector as well as in many other sectors. While foreign trade volume expands, especially in developing countries, in countries with a low export-to-import ratio, foreign dependency has increased. Therefore, it negatively affected the macroeconomic indicators of countries with foreign trade deficit. One of most important of these indicators is unemployment. Unemployment is not only an economic problem, but also a social problem. The group that is most affected by the consequences of the unemployment phenomenon affecting the world economies is the youth who will shape the future. It is known that youth unemployment, which refers to unemployment in the 15-24 age range, is 2-3 times higher than adult unemployment in developed and developing countries. This situation negatively affects the lives of young people and causes important problems in the economic structure of countries and threatens the future of economies. The aim of this study is to examine the effects of foreign trade volume, which has increased especially with the effect of globalization, on youth unemployment in G-8 countries. For this purpose, annual data of the period 1996-2018 were used in the study. In the study, firstly, the cross-section dependency test was applied for the variables and according to the obtained result, CADF unit root test, which is one of the second-generation panel unit root tests, was used. Later, panel bootstrap cointegration test developed by Westerlund and Edgerton (2007) was used. Finally, as a result of determining the cointegration relationship, the long-term cointegration vector was estimated by the CCE estimator. According to the findings, it was concluded that for the panel in general, a %1 increase in the foreign trade volume in the G-8 countries reduced youth unemployment by 0.19 units.
Keywords: Foreign Trade Volume; G-8 Countries; Youth Unemployment; Panel Data Analysis; CCE Estimator